ABOUT THE PERSON. CONCEPTS IN LIZA - Palomar Maldonado, Evaristo (2019)
With a normative presence, both international and national, in crescendo since the end of the Second World War, the statement “dignity of the human person” leads us to some perplexity, given that we are presented in the reading of two approaches that With identity of expression in language, however, they carry radically opposed meanings. The present work outlines the two currents and their contents of significance from the outstanding contribution of prof. Ribas about the person name in the Roman tradition.